Infodemiological study of the COVID-19 pandemic association in Brazil and the volume of internet search (Research, Society and Development, 2021)
To verify the existence of a relationship between the search for information on the Internet about COVID-19 and the number of cases and deaths caused by the disease in the Brazilian territory. We performed an infodemiological study using the search word “Coronavirus” on Google Trends™, for each federative unit and the Federal District, referring to the population, the number of confirmed cases and the number of deaths. We then compared each Research Volume Relating to the number of new cases and deaths from COVID-19 reported by the Ministry of Health of Brazil during the period from May to June 2020. The first cases of COVID-19 reported in the country were accompanied by an increase in Internet searches on the subject, with a reduction in interest over the period studied. The average Relative Research Volume was 37.8. There was a positive correlation between cases and deaths, however the correlation between these parameters and the Relative Research Volume behaved with negative significance. Infodemiological data have allowed real-time monitoring of outbreaks of infectious diseases at local and global levels. Brazil showed the opposite behavior to previous studies. We evidenced a strong negative relationship between access to content on the Internet and the number of confirmed cases and deaths from COVID-19 throughout the Brazilian territory.